2021
DOI: 10.1021/acsbiomaterials.1c00031
|View full text |Cite
|
Sign up to set email alerts
|

A Light Activated Glucagon Trimer with Resistance to Fibrillation

Abstract: In this work, we have brought the release of glucagon under the control of light. The aim of this approach is to allow minimally invasive, two-hormone control of blood glucose. Glucagon has two major challenges associated with its therapeutic application: (1) the required amount and timing of glucagon release is highly variable, and (2) glucagon rapidly fibrillates in solution, forming aggregates that are inactive. We have developed a light activated glucagon trimer, in which we have joined three glucagon mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Previous experience suggested that the three products correspond to the three amino groups present in insulin and that the major isomer-3 was due to the modification of the sole lysine present (previously shown to be the most reactive site). 17,21 To confirm the nature of isomer-3, we subjected it to proteolysis via Glu-C, which cleaves on the carboxyl side of the glutamic acid residues. In HPLC we observed four main products, labeled 1 through 4 (Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous experience suggested that the three products correspond to the three amino groups present in insulin and that the major isomer-3 was due to the modification of the sole lysine present (previously shown to be the most reactive site). 17,21 To confirm the nature of isomer-3, we subjected it to proteolysis via Glu-C, which cleaves on the carboxyl side of the glutamic acid residues. In HPLC we observed four main products, labeled 1 through 4 (Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interaction with disordered macromolecules will retain the polarization of the emitted light. Fluorescence polarization also allows HTS and therefore is a useful technique in IDP drug discovery. , Aggregation inhibitors may be screened using fluorescence-based assays for the determination of aggregation kinetics, which is an easy and inexpensive approach for HTS . While CD spectroscopy can help determine the drug-induced changes in IDP structure, its use is limited by its sensitivity.…”
Section: Experimental Techniques In Use To Study Idpsmentioning
confidence: 99%
“… 86 , 87 Aggregation inhibitors may be screened using fluorescence-based assays for the determination of aggregation kinetics, which is an easy and inexpensive approach for HTS. 88 While CD spectroscopy can help determine the drug-induced changes in IDP structure, its use is limited by its sensitivity. CD is also sensitive to the types of buffers and salts used, making its adoption difficult for HTS.…”
Section: Experimental Techniques In Use To Study Idpsmentioning
confidence: 99%
“…The enzymatic active site or a binding interface of a POI are the target sites for installation of caging groups. Decaging occurs when these functional groups are exposed to specific physical or chemical stimuli including small molecules, light, metal ions, or enzymes. Unnatural amino acids (UAAs) present bioorthogonal functionalities for easy and site-specific incorporation of caging groups. Alternatively, caged residues can be directly introduced at desired sites in the POI using genetic code expansion (GCE) and specific stimuli can be used to decage these residues on demand. UAAs were also introduced in proteins to permit cleavage of the peptide backbone at specific sites with an appropriate stimulus .…”
Section: Modes Of Regulationmentioning
confidence: 99%